Revisão taxonômica das espécies do gênero Trachelyopterichthys Bleeker, 1862 (Siluriformes: Aucheripteridae). - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
The species of Trachelyopterichthys were reviewed. Specimens available at museums were analyzed, as well as comparisons of original descriptions. The validity of the species was tested by means of statistical comparisons of measurements and counts and qualitative analyzes of internal and external anatomy. The representatives of Trachelyopterichthys are distributed in tributaries of the Amazon and Orinoco river basins. Three valid species are recognized in the genus, one of them new to science. Trachelyopterichthys taeniatus, type species of the genus, is the most widely distributed representative. Trachelyopterichthys anduzei is restricted to the Orinoco River basin. A dichotomous key for identification of valid species of the genus is provided
Keywords: Toxonomia; Diversidade; Peixe; CNPQ: GEOCIÊNCIAS; RECURSOS NATURAIS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSTECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO